Pengelolaan Dana Desa Berbasis Ekonomi Syariah sebagai Instrumen Pemberdayaan Masyarakat Lokal - Luluk Nikmatus Sholikhah; Ifdlolul Maghfur; M Dayat (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the effect of sharia-based village fund management on local community empowerment and to identify its contribution to improving community welfare. The study employed a quantitative approach, with data collected through questionnaires administered to community members as respondents. The data were analyzed using simple linear regression to examine the effect of sharia-based village fund management on local community empowerment. The results show that sharia-based village fund management has a positive effect on local community empowerment. The implementation of transparency, accountability, community participation, justice, and public interest principles in village fund management encourages community involvement in development and strengthens economic empowerment and community welfare. These findings indicate that sharia-based village fund management functions not only as a mechanism for managing village finances but also as an instrument for community empowerment that can direct village development toward public interest, community self-reliance, and sustainability. The findings further indicate that integrating Islamic economic values into village fund management can broaden the benefits of village funds for local communities, particularly by increasing participation, strengthening economic capacity, and addressing social needs